Preliminary late Miocene palynomorph assemblages from the Quifangondo and Luanda formations, Onshore Kwanza Basin, Angola. (June 2021) - Rodrigues, C.F.; Pereira, Z.; Mendes, M.; Nsungani, P.C.; Fernandes, P.; Lopes, G.; Duarte, L.V.; Aboelkomsan, W.; Taylor, E.; Tyrrell, M.; Fernando, M.F.; Machado, V.
Abstract: A Miocene succession exposed at the Cabo Ledo and Miradouro da Lua sections in the Onshore Kwanza Basin, Angola, was examined for palynology. Palynomorphs of preliminary late Miocene age identified are presented herein. The upper part of the Quifangondo Formation is dated as middle Tortonian in age based on the co-occurrence of the pollen grain Fenestrites spinosus and the dinoflagellate species Selenopemphix armageddonensis. The palynomorph signature indicates a middle neritic marine environment dominated by dinoflagellate cyst taxa. A late Miocene (late Tortonian to Messinian) age is also documented for the first time at the base of the Luanda Formation based on the co-occurrence of the pollen taxa Echitricolporites spinosus, Fenestrites spinosus, Fenestrites longispinosus, Monoporopollenites annulatus, and Retistephanocolpites gracilis . The palynomorph signature of this unit reflects an inner neritic marine (coastal/lagoon transitional) environment dominated by terrestrial palynomorphs and very rare dinoflagellate cyst taxa. The present research contributes data for improving the stratigraphical framework of the Quifangondo and Luanda formations, both of which are recognized as the main potential source rocks and reservoirs of the Post-Salt Paleogene/Neogene Petroleum System of the Kwanza Basin. This significant contribution provides important biostratigraphic and palaeoenvironmental data for defining the vital temporal horizons of these settings in a basin where petroleum exploration is of interest. Highlights: Preliminary palynostratigraphic ages of the Quifangondo and Luanda formations. Palaeoenvironmental interpretation based on palynomorphs. Improvement of the Miocene Kwanza Basin stratigraphy. Contribution to the key temporal horizons of the Post-Salt petroleum system.